Service Quality and Security in Ugandan E-Banking: Implications for Customer Satisfaction: A Systematic Literature Review - Kassim, Mukuuma; Mujinga, Mathias (Universitas Bina Darma, 2024)
The rise of e-banking has significantly transformed the banking industry, introducing new dimensions of quality of service and customer satisfaction. However, existing studies have primarily focused on these aspects from a global perspective, with limited emphasis on the Ugandan context. This research aims to synthesize existing knowledge and identify key factors for developing a framework to enhance e-banking quality of service, security, and customer satisfaction in Uganda through a systematic literature review (SLR), guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. The review follows a structured approach involving the identification, screening, eligibility, and inclusion stages as per PRISMA. A comprehensive search strategy across databases resulted in the inclusion of 21 studies out of an initial 103 articles. The findings reveal vital dimensions such as reliability, responsiveness, system availability, and privacy, among others, for enhancing e-banking quality of service. This study provides valuable insights for both academic and practical applications, emphasizing the need for context-specific research and laying the groundwork for future studies in the Ugandan e-banking sector.